JOURNAL OF GOVERNMENT & POLITICS : An Analysis of Local Power Structure of Thailand : Evolution and Implications - Sataporn Roengtam (FISIPOL UMY, 2016)
This study presents the results of the investigation about the current characteristic, composition and relationship of actors in the 'Power Structure of Thailand'.